Contingent Capital : Economic Rationale and Design Features - Pazarbasioglu, Ceyla; Le Lesle, Vanessa; Moore, Michael; Zhou, Jianping (Washington, D.C. : International Monetary Fund, 2011)
The causes of the global financial crisis were multi-faceted but revealed still unresolved weaknesses in national and international financial oversight and resolution frameworks. In particular, many governments in the crisis-hit countries had to provide unprecedented levels of support to contain the crisis and protect financial stability. These interventions have not only contributed to a significant increase in sovereign exposures but, in many countries, they have also risked weakening market discipline and worsening moral hazard.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet